2018
DOI: 10.3390/cancers10070217
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Pulse Stimulation for the Treatment of Pancreatic Cancer and the Changes in Immune Profile

Abstract: A Pancreatic cancer is a notorious malignant neoplasm with an extremely poor prognosis. Current standard of care is rarely effective against late-stage pancreatic cancer. In this study, we assessed nanopulse stimulation (NPS) as a local treatment for pancreatic cancer in a syngeneic mouse Pan02 pancreatic cancer model and characterized corresponding changes in the immune profile. A single NPS treatment either achieved complete tumor regression or prolonged overall survival in animals with partial tumor regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 37 publications
3
30
0
Order By: Relevance
“…The nanosecond pulsed electric field is an emerging locoregional electric ablative therapy that can be used to treat a variety of solid tumors, including melanoma [17], breast cancer [18], colon cancer [11], osteosarcoma [19], pancreatic cancer [20] and hepatocellular carcinoma [21]. The nonthermal characteristic and avoidance of heatsink effects are two of the most significant features of nsPEF ablation, which makes it possible to apply nsPEF ablation on liver tumors located near vital structures such as the porta hepatis.…”
Section: Discussionmentioning
confidence: 99%
“…The nanosecond pulsed electric field is an emerging locoregional electric ablative therapy that can be used to treat a variety of solid tumors, including melanoma [17], breast cancer [18], colon cancer [11], osteosarcoma [19], pancreatic cancer [20] and hepatocellular carcinoma [21]. The nonthermal characteristic and avoidance of heatsink effects are two of the most significant features of nsPEF ablation, which makes it possible to apply nsPEF ablation on liver tumors located near vital structures such as the porta hepatis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vivo findings provide greater mechanistic insight into the types of cell death induced by nsPEFs (118)(119)(120). Based on the inflammatory and immunomodulatory conditions, these studies reveal that nsPEFs may induce programmed necrosis or necroptotic cell death in breast, melanoma, and pancreatic cancers (118)(119)(120).…”
Section: Nanosecond Pulsed Electric Fields (Nspefs)mentioning
confidence: 99%
“…Several recent studies have revealed that IRE and other electroporation-based tumor ablation modalities significantly alters the tumor microenvironment and immune system activation (21,(24)(25)(26)(27)(28). In general, these studies show that irreversible electroporation results in a shift in the immunosuppressive tumor microenvironment to one that is more pro-inflammatory and anti-tumorigenic.…”
Section: Ire Treatment Impacts Critical Hallmarks Of Pancreatic Cancermentioning
confidence: 99%